The role of simulation to support donation after circulatory death with extracorporeal membrane oxygenation (DCD-ECMO). (November 2017) - Puślecki, Mateusz; Ligowski, Marcin; Dąbrowski, Marek; Sip, Maciej; Stefaniak, Sebastian; Kłosiewicz, Tomasz; Gąsiorowski, Łukasz; Karczewski, Marek; Małkiewicz, Tomasz; Ładzińska, Małgorzata; Zieliński, Marcin; Pawlak, Aleksander; et al.
Maintaining the viability of organs from donors after circulatory death (DCD) for transplantation is a complicated procedure, from a time perspective in the absence of appropriate organizational capabilities, that makes such transplantation cases difficult and not yet widespread in Poland. We present the procedural preparation for Poland's first case of organ (kidney) transplantation from a DCD donor in which perfusion was supported by extracorporeal membrane oxygenation (ECMO). Because this organizational model is complex and expensive, we used advanced high-fidelity medical simulation to prepare for the real-life implementation. The real time scenario included all crucial steps: prehospital identification, cardiopulmonary resuscitation (CPR), advanced life support (ALS); perfusion therapy (CPR-ECMO or DCD-ECMO); inclusion and exclusion criteria matching, suitability for automated chest compression; DCD confirmation and donor authorization, ECMO organs recovery; kidney harvesting. The success of our first simulated DCD-ECMO procedure in Poland is reassuring. Soon after this simulation, Maastricht category II DCD procedures were performed, involving real patients and resulting in two successful double kidney transplantations. During debriefing, it was found that the previous simulation-based training provided the experience to build a successful procedural chain, to eliminate errors at the stage of identification, notification, transportation, donor qualifications and ECMO organ perfusion to create DCD-ECMO algorithm architecture.